2017
DOI: 10.1021/acs.analchem.7b02290
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted LC-MS/MS Profiling of Cell Culture Media Formulations for Evaluation of High Temperature Short Time Treatment Effects

Abstract: An untargeted LC-MS/MS platform was implemented for monitoring variations in CHO cell culture media upon exposure to high temperature short time (HTST) treatment, a commonly used viral clearance upstream strategy. Chemically defined (CD) and hydrolysate-supplemented media formulations were not visibly altered by the treatment. The absence of solute precipitation effects during media treatment and very modest shifts in pH values observed indicated sufficient compatibility of the formulations evaluated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Floris et al . used nontarget MS to investigate the thermal stability of media during high‐temperature short‐term (HTST) sterilization, focusing particularly on Maillard products …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Floris et al . used nontarget MS to investigate the thermal stability of media during high‐temperature short‐term (HTST) sterilization, focusing particularly on Maillard products …”
Section: Introductionmentioning
confidence: 99%
“…32 Floris et al used nontarget MS to investigate the thermal stability of media during high-temperature short-term (HTST) sterilization, focusing particularly on Maillard products. 33 Among the multiple factors that are critical for CDM component stability, experience from 12 000-L scale manufacturing showed that preparation temperature is one of the main factors contributing to interbatch variability (unpublished data). This is based on the lack of temperature control in qualified medium preparation tanks.…”
Section: Introductionmentioning
confidence: 99%
“…25,31,32 Floris et al reported that heat treatment of CHO media formulations was associated with increased presence of Maillard products, particularly for hydrolysate-supplemented formulations, which introduce more carbohydrates and amino-acids. 33 Furthermore, Weaver and Rosenthal observed that a medium containing fetal bovine serum was not compatible with heat treatment. 34 However, as HTST was not performed on the same medium without serum, it cannot be assessed whether this incompatibility came from the serum itself or another component of the basal medium.…”
Section: Impact On Culture Mediamentioning
confidence: 99%
“…35 Among them, some are known to be owned by Amgen, and Biomarin. 26,29,33,34,36 Eli Lilly also showed interest in this technology with a study at small-scale. 24 The Life Science business of Merck KGaA offers the opportunity for outsourcing HTST treatment of high-risk raw materials such as glucose at their two redundant large-scale production sites.…”
Section: High Temperature Short Time Treatment In the Biopharmaceutical Industrymentioning
confidence: 99%
“…It is standard practice to maintain CCM at 4 • C prior to use, but the design of hydrated CCM that are stable at room temperature (RT) may decrease the energy consumption by eliminating the need for refrigeration. This optimization of CCM stability involves both developing methods to detect critical changes to CCM that can negatively impact cell culture [3,4] and using this information to discover strategies to mitigate such changes.…”
Section: Introductionmentioning
confidence: 99%